Behavior Based Safety Implementation Using the DO IT Method at Pertamina in Makassar City - Baharuddin, Alfina; Fachrin, Suharni A.; Putri , Widya Eka (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
The application of Behavior Based Safety (BBS) in an effort to reduce the potential risk of accidents has been widely applied in various industries. However, its application with the DO IT (Define, Observed, Intervene Test) method to change unsafe behavior is still rarely implemented. The purpose of the research is how to identify the stages of implementing Behavior Based Safety (BBS) with the DO IT method, what forms of intervention are given in an effort to modify worker behavior for Pertamina officers in of Makassar. This type of research is quantitative with an observational approach. With behavior-based safety using the DO IT method Data collection is done by observation, reviewing documents, and interviews. The Observe stage is to observe the behavior that has been determined, obtained an initial score that the rate of PPE application among the workers was 66,6%. most workers had shown safe behavior (56,6%). Safety briefing was conducted at the Daily Section of the Pertamina. The results, it was found that, with regard to the compliance with operation procedure , most workers had shown safe behavior (53,3%). Based on the research results, the DO IT method is an effective and efficient method for industries that do not yet have a good occupational safety and health management system in a company. This study recommends that companies apply the do it method and strengthen oversight and monitoring related to safety behavior in preventing work accidents and increasing employee work productivity.